PENDIDIK MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN SERTA PELATIH KEPEMUDAAN DAN KEPRAMUKAAN PADA SATUAN PENDIDIKAN FORMAL DAN/ATAU NONFORMAL : STUDI PADA GURU MENJAHIT DI SKB KABUPATEN BOGOR - Hafiz Rizky; Holva Lovana Siregar (SINERGI : Jurnal Riset Ilmiah, 2026)
Professional ethics is an important foundation for the implementation of the duties of educators and education personnel, both in formal and non-formal educational settings. Teachers of Craft and Entrepreneurship (PKWU) subjects, as well as youth and scouting trainers, play a strategic role in developing students' skills, independence, and character. This article aims to examine the implementation of professional ethics among PKWU educators through a study of sewing teachers at the Learning Activity Center (SKB) in Bogor Regency, a non-formal educational institution. This research used a descriptive qualitative approach, with data collection techniques through observation and interviews with sewing teachers and SKB administrators. The results indicate that the application of professional ethics is reflected in attitudes of responsibility, discipline, humanistic service, and the educators' commitment to patiently and professionally guiding students. Professional ethics plays a crucial role in improving the quality of sewing skills learning, building student trust, and supporting community empowerment through non-formal education.